Peran Street Level Bureaucracy Dalam Implementasi Kebijakan Perlindungan Lahan Pertanian Pangan Berkelanjutan Di Kota Makassar - Muhlis Madani; Muhammad Irvan Nur Iva; Iswadi Amiruddin (Kolaborasi : Jurnal Administrasi Publik, 2021)
AbstractStreet level bureaucrats are frontline bureaucrats who interact directly with the public or provide direct services to the community. This study aims to analyze the role of the street level bureaucracy in the implementation of sustainable food agricultural land protection policies in the city of Makassar. The method used in this research is qualitative with case study type. The data collection process is done through observation, interviews and documentation. Research informants consisted of stakeholders, frontline bureaucrats and farmers who were selected by purposive sampling. Then data analysis techniques through data reduction, data presentation, and drawing conclusions. The results showed that the role of the street level bureaucracy in the implementation of sustainable agricultural land protection policies carried out by the Makassar City Agriculture Office included the role of supervisor and monitoring of the protection of food agricultural land. Technically, the Department of Agriculture and Fisheries, through field officers, conducts regular monitoring of farmer activities. In addition, they also play a role in receiving reports on farmers' added area and reporting to the service every week. As for those who play a role in providing assistance and technical agricultural counseling are carried out by Field Agricultural Instructors.Keywords: Street level bureaucrats, policy implementation, agricultural land protection